Síntese e propriedades de Ce1-xGdxO2-x/2 (x=0;0,1 e 0,2) obtidos pelo método hidrotermal assistido por micro-ondas - Carregosa, João Domingos Covello (2017)
The solid solution of Gd3+ doped CeO2 (GDC) is a promising candidate for electrolyte in SOFCs (Solid Oxide Full Cells) operating in intermediate and low temperatures. The reduction of the working temperature of these energy conversion devices is the great technological challenge to its marketing. In this work, nanocrystalline powders of Ce1-xGdxO2-x/2 with x=0; 0.1 e 0.2 were obtained by microwave-assisted hydrothermal synthesis at low temperature and times of synthesis (10 and 20 min at 120 °C). The powders were analyzed by TG-DTA, SEM, XRD and dilatometry. The results showed characteristic peaks of the cubic fluorite structure, referring to the cerium oxide (CeO2), without the presence of secondary peaks. We also observed that the samples synthesized at 10 and 20 minutes showed distinct behaviors in function of the concentrations of Gd3+. In addition, immersion tests were performed for the sintered ceramics, by Archimedes method. The relative density values were above 92% for all the proposed formulations.